TUTURAN MAKIAN DALAM FILM CROWS ZERO DAN MY BOSS MY HERO: KAJIAN -PRAGMATIK - Yuni Darma Santi (LP2M IAIN Tulungagung, 2017)
This research is aim to study the information of swearing speech inthe view of cooperation principle and courtesy principle and also therelationship between obedient in principle of cooperation and courtesyprinciple. This research is the qualitative research. The method usedin this research is descriptive analysis. Data source in this researchare the films of Crows Zero and My Boss My Hero. The dataresearch is in the form of swearing speech both obedience and alsodisobedience to the principle of politeness cooperation. The Techniqueof data collecting uses the technique of correct reading and note. Theresult of this research shows the swearing speech in the view ofcooperation principle, there are swearing speech which disobey, that isdisobedience of quantity maxim pursuant to circumstance of reference,consanguinity and object; disobedience of quality maxim pursuant toprofession reference; disobedience of relevancy maxim pursuant toreference of the state of animal, ghost, part of body and profession;disobedience of execution maxim pursuant to profession maxim pursuant to profession reference; obedient to execution maximpursuant to reference of the state of animal, profession and kinship.Swearing speech in the view of politeness principle, there are swearingspeech which disobey, that is disobedience of wisdom maxim pursuantto reference of the state and part of body; disobedience of philanthropymaxim pursuant to profession reference; disobedience of praise maximpursuant to reference the state of animal, ghost, part of body andprofession; disobedience of humility maxim pursuant to animalreference; disobedience of general consensus maxim pursuant to animalreference and part of body. Then, swearing speech obedience topoliteness principle is obedient to wisdom maxim pursuant toprofession reference; obedient to philanthropy maxim pursuant tocircumstance reference; obedient to praise maxim pursuant to referenceof a circumstance ; obedient to humility maxim pursuant to referenceof a circumstance.Keywords: Swearing speech reference.Then, swearing speech that obeys cooperation principle is obedient toquality maxim pursuant to profession reference; obedient to relevancy